Emotional Recognition in Patients With Mesial Temporal Epilepsy Associated With Enlarged Amygdala - Kuchukhidze, Giorgi; Unterberger, Iris; Schmid, Elisabeth; Zamarian, Laura; Siedentopf, Christian Michael; Koppelstaetter, Florian; Gizewski, Elke; Kronbichler, Martin; Luef, Gerhard; Jokeit, Hennric; Trinka, Eugen (Frontiers in Neurology, 2022)
Background: Amygdalae play a central role in emotional processing by interconnecting frontal cortex and other brain structures. Unilateral amygdala enlargement (AE) is associated with mesial temporal lobe epilepsy (mTLE). In a relatively large sample of patients with mTLE and AE, we aimed to evaluate functional integration of AE in emotion processing and to determine possible associations between fMRI activation patterns in amygdala and deficits in emotion recognition as assessed by neuropsychological testing. Methods: Twenty-two patients with drug resistant unilateral mTLE due to ipsilateral AE were prospectively recruited in a large epilepsy unit and compared with 17 healthy control subjects in terms of amygdala volume, fMRI activation patterns and performance in emotion recognition as assessed by comprehensive affect testing system (CATS) and Ekman faces. All patients underwent structural and functional 1.5 Tesla MRI, electro-clinical assessment and neuropsychological testing. Results: We observed BOLD signal ipsilateral to AE (n=7; group PAT1); contralateral to AE (n=6; group PAT2) and no activation (n=9; group PAT3). In the region of interest (ROI) analysis, beta estimates for fearful face > landscape contrast in the left amygdala region did not differ significantly in patients with left TLE vs. patients with right TLE (T(16)=-1.481; p=.158). However, beta estimates for fearful face > landscape contrast in the right amygdala region were significantly reduced in patients with right TLE vs. patients with left TLE (T(16)=-2922; p=.010). Patients showed significantly lower total scores in CATS and Ekman faces compared to healthy controls. Conclusion: In our cohort, patients with unilateral mesial TLE and ipsilateral AE, an amygdala could display either functional integration in emotion recognition or dysfunction as demonstrated by fMRI. Perception and recognition of emotions were impaired more in right-sided mTLE as compared to left-sided mTLE. Neuropsychological tests showed deficits in emotion recognition in patients as compared to healthy controls.